EVALUATING THE PROCESS OF ELECTRONIC ID CARD (E-KTP) SERVICES AT THE POPULATION ADMINISTRATION AND CIVIL REGISTRATION OFFICE OF LEBAK BULUS SUBDISTRICT - Silitonga, Irvan Pangihutan; Permana, Djaka; Budiastra, A. A., Ketut (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2024)
This research aims to evaluate the electronic Identity Card (e-KTP) issuance service at the Population Administration and Civil Registration Office of Lebak Bulus Subdistrict, referring to the Decision of the Head of the Population and Civil Registration Office of DKI Jakarta Province Number 100 of 2022, which establishes service standards. This research utilizes a qualitative descriptive approach, based on observations and in-depth interviews, and relates it to operational concepts, frameworks, and relevant laws. The evaluation results indicate that the e-KTP service has successfully optimized service time, with an average waiting time of approximately 10-15 minutes, which is a strength of the service. However, there are several challenges in verifying population data and technical issues with hardware usage. Although the staff provides good service, there is a lack of clear information regarding the status of e-KTP application progress for applicants. Recommendations for improvement include enhancing recording facilities, improving communication with applicants, maintaining hardware, and enhancing cooperation with relevant agencies. This research contributes to efforts to enhance the quality of e-KTP issuance services and provides guidance for similar institutions in improving service effectiveness and efficiency.